Pathways to Health - Ploubidis, George B.; Pongiglione, Benedetta; De Stavola, Bianca; Daniel, Rhian; Benova, Lenka; Grundy, Emily; Read, Sanna; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2019)
This book presents a rigorous enquiry into life course processes that are thought to influence health, integrating the latest methodologies for the study of pathways that link socio-demographic circumstances to health with an emphasis on the mediating factors that lie on these pathways. Following an introductory chapter on the application of formal mediation methods within the life course framework, the book offers insights on the pathways that link early life socio-economic circumstances to physical activity in later life, the role of physical activity as a moderator and/or mediator of the association between fertility history and later life health and the evolution of self-rated health over the life course in two generations born 12 years apart in 20th century Britain. Pathways to Health presents a dynamic view on how to investigate specific hypotheses within the life course framework and enhances the ability of the social science community to investigate specific mechanisms related to public health interventions.
Mediation Analysis for Life Course Studies: Bianca De Stavola & Rhian Daniel -- Lifelong socio-economic position and later life health related behaviour: A formal mediation approach: George B. Ploubidis, Lenka Benova, Bianca DeStavola & Emily Grundy -- Physical activity: a moderator or mediator in the association between fertility history and later life health?: Sanna Read & Emily Grundy -- Self-rated health over the life course: Evidence from the 1958 and 1970 British birth cohorts:George B. Ploubidis & Benedetta Pongiglione.
Keywords: Life cycle, Human; Public health; Demography; Population; Epidemiology; Life Course; Public Health; Population and Demography; Epidemiology